PEMANFAATAN BUDIDAYA LELE DAN HIDROPONIK SEBAGAI SUMBER PROTEIN ALTERNATIF UNTUK MENCEGAH STUNTING DI DESA SELODAKON - Illahi, Fahri Agustama Nur; Uyun, Ulfatul; Wasana, Arka Tri Labda; Camelia, Atika Nora; Wahyuni, Emelia Ayu; Istiqomah, May; Effendi, Moh Dion; Maulida, Putri; Santosa, Syifa Ulinnuha; Badzlin, Safira; Wicaksana, Muhammad Iqbal; Nungtias, Ayu Setya; Cloudia, Cindy Ade; handayani, ririn (Politeknik Kesehatan Kemenkes malang, 2023)
The community service was conducted in Selodakon village, which is in the Tanggul sub-district, Jember Regency. The purpose of this community service activity is to identify the root causes of stunting in Selodakon Village and propose concrete solutions that can be implemented in efforts to prevent and overcome stunting. Activities undertaken include catfish farming and hydroponics as an effort to prevent stunting. The activities of this community service began with socializing the work program to the community and then holding demonstrations in making media and how catfish and hydroponic cultivation work. The activity ended with the handing over of the media to Selodakon village.